ASSESSING ECOLOGICAL AWARENESS LEVELS: A NEW MULTI-DIMENSIONAL CONCEPTUAL FRAMEWORK (Eurasian Journal of Ecology, 2022)
Assessments of ecological awareness levels are immensely crucial in ecological awareness studies, especially for a developing country like Kazakhstan, which has struggled and is still struggling to address various environmental problems ranging from the Aral Sea to water deficiency matters. While many scholars have addressed the specific aspects of environmental problems such as air and water pollution, there is limited amount of work on addressing ecological awareness levels among the general popula-tion by local Kazakhstani scholars. This paper’s research objective was to propose a new conceptual framework for assessing ecological awareness levels. It consisted of four main dimensions: cognitive, af-fective, altruistic and conative dimension, for which each of the following dimensions different research instruments were introduced. For that, the paper extensively researched, emulated and re-applied the theoretical frameworks and concepts of the works of Western scholars. The aim of this research is to fill the research gap on the lack of conceptual frameworks in assessing the general public’s level of ecologi-cal awareness in Kazakhstan. The results obtained from this paper was the introduction of a new multi-dimensional framework and the applicability of three new research instruments for future academic studies in the context of Kazakhstan. These new research tools included the 15-item EEV Scale Model, 26-item Environmental Risk Perception Scale Model, and the 18-item EAS Model. This paper provided researchers with immensely valuable research instruments for pinpointing differences in environmental values, beliefs, concerns, and perceptions of different sample populations in Kazakhstan.Key words: Kazakhstan; ecological awareness; conceptual framework; assessment dimensions.